Jockeying for Position in CEO Letters: Impression Management and Sentiment Analytics. Issue 1 (17th April 2018) - Boudt, Kris; Thewissen, James
Abstract: This paper evidences the strategic positioning of positive and negative words within a CEO letter as a subtle form of impression management. We find that managers tend to present information in such an order that the reader of the CEO letter has a more positive perception of the underlying message. We uncover a smile in the frequency of positive words within the letter, and a half smile in the intratextual distribution of negative words, with a prevalence of negative words at the beginning of the letter. We also find a significant positive association between this qualitative impression management and the use of abnormal accruals in earnings management. We propose sentiment analytics that can compensate for the strategic management of narrative structure and find that the proposed position weighted sentiment has more predictive power for the firm performance over the next year.